Competitive balance and attention level effects: Theoretical considerations and preliminary evidence - Tim Pawlowski; Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2014)
We try to better understand possible reasons for deviations between statistically-measured competitive balance (CB) and perceived CB. Moreover, we suggest answers to the following questions: are there specific dimensions of CB that are perceived to be significantly less balanced in the Danish Superligaen compared to the other two leagues? Are there objective measures that confirm the fans' perception or does OCB in general deviate from PCB?
Keywords: 330; competitive balance; sports economics; behavioural economics; mid-term outcome uncertainty; fan perception